Integrasi Prinsip Ekonomi Islam dan Good Corporate Governance dalam Tata Kelola Global Berkelanjutan - Dodi Sunanto; Ela Nurlaela; Aisya Anik Farida Musa; Aan Jaelani; Dewi Fatmasari (BISMA : Business and Management Journal, 2026)
Global economic inequality, environmental crises, and weak accountability in international governance have highlighted the need for a more equitable and sustainable governance paradigm. This study aims to analyze the integration of Islamic economic principles with Good Corporate Governance (GCG) as a conceptual framework for achieving global governance that promotes sustainable economic justice. A qualitative approach was employed using an integrative literature review of 30 selected scholarly articles systematically identified through the PRISMA guidelines from the Scopus, ScienceDirect, Springer, and Google Scholar databases. The data were analyzed using content analysis and thematic analysis to synthesize the relationships among maqāṣid al-sharī‘ah, GCG principles, Islamic financial instruments, and the Sustainable Development Goals (SDGs). The findings reveal that integrating maqāṣid al-sharī‘ah with the principles of transparency, accountability, responsibility, independence, and fairness enhances economic inclusiveness, equitable wealth distribution, and social and environmental sustainability through the optimization of Islamic banking, zakat, waqf, and Islamic microfinance. The study concludes that integrating Islamic Economics and GCG offers a viable alternative paradigm for a more equitable, inclusive, and sustainable global governance system. The findings also imply the need for regulatory harmonization, the development of maqāṣid-based governance indicators, and stronger public policies and international collaboration to support the implementation of value-based global governance. Global economic inequality, environmental crises, and weak accountability in international governance have highlighted the need for a more equitable and sustainable governance paradigm. This study aims to analyze the integration of Islamic economic principles with Good Corporate Governance (GCG) as a conceptual framework for achieving global governance that promotes sustainable economic justice. A qualitative approach was employed using an integrative literature review of 30 selected scholarly articles systematically identified through the PRISMA guidelines from the Scopus, ScienceDirect, Springer, and Google Scholar databases. The data were analyzed using content analysis and thematic analysis to synthesize the relationships among maqāṣid al-sharī‘ah, GCG principles, Islamic financial instruments, and the Sustainable Development Goals (SDGs). The findings reveal that integrating maqāṣid al-sharī‘ah with the principles of transparency, accountability, responsibility, independence, and fairness enhances economic inclusiveness, equitable wealth distribution, and social and environmental sustainability through the optimization of Islamic banking, zakat, waqf, and Islamic microfinance. The study concludes that integrating Islamic Economics and GCG offers a viable alternative paradigm for a more equitable, inclusive, and sustainable global governance system. The findings also imply the need for regulatory harmonization, the development of maqāṣid-based governance indicators, and stronger public policies and international collaboration to support the implementation of value-based global governance.